Manajemen Dan Keamanan Jaringan Nirkabel Berbasis Wireless Gateway Security Controlling System - Marcus, Ronald David; Prameswari, Annisa Dwi (J-INTECH (Journal of Information and Technology), 2024)
Along with the development of the internet today, especially the use of WiFi Networks that are already available in various places, forcing network owners or admins to be able to optimize and maintain network traffic to remain stable and secure. Where the security system used must consider the number of users and the area of ​​the network needed. In this study, the author implemented a system that collaborates the UniFi Unify Wireless Controller and Mikrotik Router to optimize Wireless Services to make it easy and safe for users. The approach used in this study is a qualitative approach. The steps that have been taken for the qualitative method approach are conducting a location survey, designing the topology based on the results of the location survey and implementing it directly into a wireless network system with support from the Unify UniFi Wireless Controller and Mikrotik Router, where in this topology it can monitor, manage and control wireless devices in large numbers and controlled in one Controlling System and Gateway. The results of this study are the ease of managing Wifi Networks on a large scale. Management of large numbers of wireless devices in a centralized UniFi wireless controller system and monitoring and setting services to users centrally, both Access Rights, namely bandwidth quotas and access times which are also centralized. Of course, this will make it easier for admins to manage wireless networks on a large scale.